Review of the genus Paramesius Westwood, 1832 (Hymenoptera: Diapriidae, Spilomicrini) from Russia, with description of four new species - Chemyreva, Vasilisa G.; Kolyada, Victor A. (Zootaxa, 2018)
A review of the eight Palaearctic species of the genus Paramesius Westwood is provided, four of which are described and illustrated: P. primorus Chemyreva et Kolyada, sp. nov. (Russia: Primorsky Territory), P. janmaceki Chemyreva et Kolyada, sp. nov. (Russia: Primorsky Territory, Kuril Islands: Kunashir, Shikotan), P. ocampus Chemyreva et Kolyada, sp. nov. (Russia: Primorsky Territory, Sakhalin), and P. spiracularis Chemyreva et Kolyada, sp. nov. (Russia: Primorsky Territory, Khabarovsk Territory, Kuril Islands: Kunashir). New synonyms are proposed (valid name is the first): P. brachypterus Thomson, 1859 = P. spinosus Kieffer, 1911, syn. nov.; P. crassicornis Thomson, 1859 = P. dolosus Kieffer, 1911, syn. nov. = Spilomicrus kaszabi Szabo, 1977, syn. nov.; P. rufipes (Fonscolombe), 1832 = Spilomicrus striatifoveatus Szabo, 1960, syn. nov. All known Palaearctic species of Paramesius are keyed.